1978
DOI: 10.1254/jjp.28.171
|View full text |Cite
|
Sign up to set email alerts
|

Renin Inhibitory Effect of N-Acetyl-Pepstatin

Abstract: It has been demonstrated that pepstatins isolated from streptmyces inhibit the renin activity and among pepstatins and other renin inhibitory substances, pepstatin A, isovaleryl pentapeptide is known as a most potent renin inhibitor (1, 2, 3). The solubility of this compound limits application in many studies. In the present work, the renin inhibitory activity of a soluble acid protease inhibitor, N-acetyl-pepstatin, was demonstrated both in vitro and in vivo. N-acetyl-pepstatin was found in a culture filtrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
1993
1993

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Thus, the inhibitory action of Af-acetylpepstatin on renin in the vascular wall may, at least in part, contribute to its antihypertensive action. 7 The mechanism of the hypotensive effects of ACE inhibitors has been explained by their suppression of the circulating RAS. However, accumulating evidence has indicated that the consequent decrease in circulating level of plasma Ang II is probably not the sole mechanism involved.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the inhibitory action of Af-acetylpepstatin on renin in the vascular wall may, at least in part, contribute to its antihypertensive action. 7 The mechanism of the hypotensive effects of ACE inhibitors has been explained by their suppression of the circulating RAS. However, accumulating evidence has indicated that the consequent decrease in circulating level of plasma Ang II is probably not the sole mechanism involved.…”
Section: Resultsmentioning
confidence: 99%
“…This work was difficult to reproduce, probably because of the insolubility of the peptide, 37 -38 and did not lead to the widespread adoption of pepstatin in physiologic experiments. Improvements in solubility, first by acetylation of pepstatin 39 and then by the substitution of hydrophilic amino acids at the carboxy terminus of the molecule, 40 yielded more convincing results. Although pepstatin derivatives may eventually prove to be adequate in vivo renin inhibitors, their use as investigative agents is limited conceptually by their lack of specificity for renin.…”
Section: Pepstatin and Its Congenersmentioning
confidence: 99%
“…Since that time, we have focused our attention on the development of a synthetic renin inhibitor and showed that phosphatidyl and phosphorylethanolamine deriva tives (7,8) and N-acetyl-pepstatin (9) inhibited the renin activity and lowered the blood pressure in hypertensive animals. Unfortunately, the potencies of these compounds were not high enough to inhibit human renin.…”
mentioning
confidence: 99%